The environmental citizenship opinions questionnaire: a self-assessment tool for secondary students - van Harskamp, Michiel; Knippels, Marie-Christine P. J.; Boeve-de Pauw, Jelle N. A.; van Joolingen, Wouter R. (Frontiers in Education, 2023)
Introduction. We present a validated instrument for assessing Environmental Citizenship (EC) of students in lower secondary education. The Environmental Citizenship Opinions (ECO) questionnaire focusses on general citizenship components, key sustainability competences, and Socio-Scientific Reasoning aspects. By combining these domains, our work provides a needed innovation as these different aspects of EC have not previously been covered in one single, balanced and validated measurement instrument. Methods. The ECO questionnaire was validated through a pilot round and a subsequent large-scale study (781 lower secondary students). Several rounds of Confirmatory Factor Analysis resulted in a final model of 38 items divided in 7 first order and 5 second order constructs. Results. The final model fit statistics indicate near excellent quality of our model (RMSEA = 0.036, CFI = 0.93, TLI = 0.93, SRMR = 0.05), which consists of EC knowledge, EC attitudes, EC skills, EC reflection and complexity of EC issues. Calculations on the relative attribution of each of the five main constructs to overall environmental sustainability citizenship, highlight that attitudes and reflection skills are the most important constituents. Discussion. Our result present the ECO questionnaire as a valuable, valid and reliable tool to measure environmental citizenship of students. Applications in practice include monitoring student's development and supporting teachers during the challenging task of effective teaching for EC in and outside the classroom.